Significance of IL36RN mutation analyses in the management of impetigo herpetiformis: A case report and review of published cases. Issue 5 (18th February 2021) - Yoshikawa, Miyuki; Rokunohe, Daiki; Kimura, Atsuko; Takahashi, Mika; Korekawa, Ayumi; Nakajima, Koji; Nakano, Hajime; Yokoyama, Minako; Tanaka, Kanji; Yokoyama, Yoshihito; Sawamura, Daisuke
Abstract: Impetigo herpetiformis (IH) is a rare variant of generalized pustular psoriasis (GPP), which develops during pregnancy. GPP is associated with mutations of IL36RN, but it is still unclear whether the same is true of IH. A 20‐year‐old Japanese woman developed erythema and pustules on her trunk during the 27th week of her first pregnancy. Within 1 month, the skin lesions spread over her whole body, accompanied by fever. Skin biopsy revealed Kogoj's spongiform pustules in the epidermis and she was diagnosed with IH. Systemic administration of prednisolone failed to resolve the skin eruption, but it was partially improved by the addition of cyclosporin. The patient gave birth to a healthy female infant. After delivery, her erythema relapsed and the effect of granulocyte and monocyte adsorption apheresis was limited. Thus, secukinumab was administrated, and since then, she has maintained complete remission. Mutation analysis revealed a homozygous c.28C>T (p.Arg10X) mutation in IL36RN . Twelve cases of IH, including that presented here, have been reported together with the results of IL36RN genetic analyses, and 10 of the 12 cases occurred in East Asia (Japan and China) despite the fact that IL36RN mutations in GPP have been reported worldwide. Among 10 IH patients of East Asian descent, seven had IL36RN mutations, all of which were founder mutations causing GPP in East Asia: c.28C>T (p.Arg10X) or c.115+6T>C (p.Arg10ArgfsX1). Thus, East Asian founder mutations may play an important role in the pathogenesis of IH. IH patients with IL36RN mutations have a tendency to require biologics to resolve postpartum flare‐ups or sustained psoriatic skin lesions. Because IL36RN mutation status may help predict postpartum flare‐ups in IH patients, mutation analysis should be considered to enable preparation for biologic therapy of intractable flare‐ups.